A study of prevalence of anemia among hypothyroidism patients and relationship between types of anemia and hypothyroidism - Bilonia, Shailendra K.; Pal, Shivangi; Charan, Karan S.; Nehra, Nikhil K. (International Journal of Research in Medical Sciences, 2022)
Background: The association between anemia and hypothyroidism has been recognized, although the prevalence of anemia in hypothyroid patients varies widely between studies. The main objectives were to study the prevalence, type, etiology of anemia in primary hypothyroidism and to correlate severity of anemia with severity of hypothyroidism. Methods: This research was conducted as a case-control study. Patients with newly diagnosed overt primary hypothyroidism and euthyroid controls totaling 170 in total were included in the study. The morphological subtypes of anemia and the causes of each were investigated. There was a correlation between the severity of anemia and that of hypothyroidism. Results: Anemia was highly prevalent among cases, as it was present in 110 (64.7%) of patients with hypothyroidism and in 60 (35.3%) of patients who did not have hypothyroidism in the control group. In cases, 100 (58.8%) of serum samples tested positive for anti-TPO, while just 20 (11.8%) of control samples did so. In these cases, with elevated TSH, the anemia was severe. Conclusions: Our study concluded that a statistically significant high anaemia prevalence was found among the patients with primary hypothyroidism. In comparison to the controls, it was shown that cases had a significantly higher incidence of certain types of, as well as anti-TPO positive and iron insufficiency. The TSH level and hemoglobin level were shown to have a statistically significant inverse association with one another.